Sorotan Literatur Perbandingan Gagasan Sastera Islami Sayyid Sayyid `Abd al-Raziq dan Mohd Affandi Hassan - Mohd Adi Amzar Muhammad Nawawi; Zulkarnain Mohamed; Pabiyah Toklubok @ Hajimaming (Pusat Kajian Usuluddin & Falsafah, UKM, 2024)
Volume 8